Claude W. Hibbard (1905-1973) - Aurele La Rocque (Hello World!, 1973)
All scientists working in Pleistocene geology and paleontology will mourn the death of Claude William Hibbard on October 9, 1973. Death came suddenly as he was preparing for the day's work in the Museum of Paleontology of the University of Michigan at a characteristically early hour. Death came some time before 8 A.M., apparently of a heart attack. Professor Hibbard, Hibbie to his friends, is survived by his wife, Fay, a daughter and two granddaughters, his mother, four brothers, and one sister.